Analisis Kebijakan Publik Dalam Meningkatkan Kualitas Pelayanan Publik Di Puskesmas Cikalong Wetan, Bandung Barat - Wiwit Kurniasih; Risalatu Mirajiah (JIAP (Jurnal Ilmu Administrasi Publik), 2021)
This study aims to analyze public policies that have been implemented in improving the quality of public services at the Cikalong Wetan Health Center, West Bandung. This study uses a qualitative descriptive method with data collection techniques through interviews, observation, and document studies. The results of the study show that the Cikalong Wetan Health Center has carried out several public policies in improving the quality of public services. One of the policies implemented is the provision of employee training and development to improve service quality. In addition, the Cikalong Wetan Health Center also measures customer satisfaction through surveys and carries out continuous improvements based on the survey results. However, there are still a number of challenges faced in the implementation of public policies at the Cikalong Wetan Health Center. The main challenge is the limited budget and available human resources, making it difficult to implement all the desired policies. In addition, there are still several service aspects that need to be improved, such as increasing service accessibility and accountability. In this case, it is suggested that the Cikalong Wetan Health Center can increase collaboration with related parties, such as the local government, NGOs, and the community, to overcome the challenges they face. In addition, the Cikalong Wetan Health Center also needs to improve budget management and human resources effectively, and continue to evaluate and improve the services provided, so as to increase customer satisfaction and achieve better public service goals.